Governing the Sustainable Development Goals in the COVID-19 era: Bringing back hierarchic styles of governance? - Simon Høiberg Olsen; Eric Zusman; Matthew Hengesbaugh; Nobue Amanuma; Shinji Onoda (Asian Development Bank Institute (ADBI), 2021)
Adopted in 2015, the 2030 Agenda for Sustainable Development and its 17 Sustainable Development Goals (SDGs) were intended to motivate governments and the international community to address the world's most pressing social and environmental challenges. However, most countries are not on pace to achieve the SDGs. The economic and human toll of the COVID-19 pandemic stands to further delay action beyond the SDGs' 2030 target date. Yet, viewed from another perspective, COVID-19 offers an opportunity to improve the governance of, and accelerate progress in, the SDGs. This paper builds upon well-established work on meta-governance to determine what changes in governance could be needed for such an outcome to materialize. More specifically, the paper employs a text analysis of keywords related to hierarchic, market, and network governance styles in high-profile SDG plans from Denmark, Japan, and Viet Nam. The text analysis demonstrates that all three countries potentially rely too heavily on market-oriented governance styles. The paper then contrasts the governance for the SDGs with a qualitative review of more hierarchic styles of governance outlined in the three countries' COVID-19 programs. The paper closes by discussing whether crises such as COVID-19 can lead to more balanced modes of governance to strengthen the political momentum on the SDGs
Keywords: O; Y; 330; governance; sustainable development goals; SDGs